Imagology profiles : the dynamics of national imagery in literature - Laurušaitė, Laura, 1981- (Cambridge Scholars Publishing, 2018)
This volume highlights the importance of imagology, one of the most popular areas of research in contemporary comparative studies. It proposes new means of academic analysis to create critical attitudes towards the development of imagological studies. The topics discussed draw a wide trajectory, from classical to marginal images, from national heroes to (un)conventional aspects of gender, from ethno-imagology to the broader dimension of intercultural references and epistemological post-poststructuralist changes. The compendium widens the field of imagology by introducing concepts such as ""geo